Comparative Effectiveness of Statins Vs PCSK9 Inhibitors in High-Risk CV patients - Atiq Ur Rehman,; Faiz Ullah,; Khan, Rahim Dil; Khan, Ajmal (Indus Journal of Bioscience Research, 2025)
Introduction: Cardiovascular disease continues to be a significant health issue, which is responsible for the highest mortality rates worldwide; dyslipidemia is an easily changeable risk factor. Statins are the first-line drugs used for the management of lipid disorders, but currently, numerous high-risk patients do not achieve LDL-C targets, which makes it necessary to use PCSK9 inhibitors. Objective: To compare the effectiveness and safety of statins versus PCSK9 inhibitors in reducing LDL-C levels and cardiovascular events in high-risk cardiovascular patients. Materials and Method: This cross-sectional study was done at Hayatabad Medical Complex Peshawar, Pakistan from March, 2024 to August, 2024. 180 high-risk patients were selected for the analysis and randomized into statin and PCSK9 inhibitor groups. Data regarding LDL-C levels, cardiovascular events, and adverse effects were examined. Results: PCSK9 inhibitors showed significantly greater LDL-C reduction (58.2% vs. 36.6%, p<0.001) and fewer cardiovascular events (6.6% vs. 15.5%, p=0.03) compared to statins. Conclusion: The study established that PCSK9 inhibitors are more potent and safer than statins for high cardiovascular risk patients.